Wingspan experience in the treatment of symptomatic intracranial atherosclerotic disease after antithrombotic failure. (27th April 2012) - Samaniego, Edgar A; Tari-Capone, Francesca; Linfante, Italo; Silva, Christine F; Spilberg, Gabriela; Gounis, Matthew; Wakhloo, Ajay K; Dabus, Guilherme
Abstract : Background and purpose: Intracranial stenting with the Wingspan system has been used as a revascularization strategy in symptomatic patients with intracranial atherosclerotic disease (ICAD). The latest results of the Stenting versus Aggressive Medical Therapy for Intracranial Artery Stenosis (SAMMPRIS) trial challenge this approach. Our experience in the treatment of symptomatic ICAD with the Wingspan system is reported. Materials and methods: Patients who underwent stenting for symptomatic ICAD were included in the analysis. Demographic data, periprocedural complications, long term radiological and clinical outcomes are reported. Results: 46 lesions were treated in 45 patients. 13 patients (29%) presented with a transient ischemic attack and 32 (71%) with a stroke. 43 patients (95.5%) failed antithrombotic therapy at presentation. One (2%) symptomatic periprocedural (24 h) complication occurred. The 30 day incidence of stroke and vascular death was 6.6%—a fatal hemorrhagic stroke and two non-fatal hemorrhagic strokes. In-stent stenosis (≥50%) was seen in nine (42.8%) lesions, two were symptomatic. Conclusions: This cohort of patients with symptomatic ICAD who failed antithrombotic medications benefited from angioplasty and stenting with the Wingspan system.